Evaluasi Kepuasan Pengguna Aplikasi My APTIKOM Melalui Pendekatan Technology Acceptance Model - Adjani, Kannisa; Hudawiguna, Sigit (Institut Teknologi Garut, 2023)
In the current era, Information Technology (IT) has become an essential need for almost all organizations, given its recognized role in increasing the efficiency and effectiveness of business processes. Associations, especially APTIKOM (Informatics and Computer Higher Education Association), also realize the importance of good IT management to achieve organizational success and achieve its goals. Therefore, evaluating user satisfaction of the My APTIKOM application is a relevant step. This research uses the Technology Acceptance Model (TAM) method to analyze the factors that influence users' attitudes towards the My APTIKOM application, namely perceptions of perceived usefulness (Perceived Usefulness) and ease of use (Perceived Ease of Use). The research results show that perceptions about the benefits of the application (Perceived Usefulness) have a significant positive influence on user attitudes (Attitude Toward Using), with a relationship level of around 47.5%. However, no significant influence was found between perceptions of ease of use (Perceived Ease of Use) and user attitudes (Attitude Toward Using), which indicates that ease of use may not be the main factor in forming users' positive attitudes towards the application. In addition, the results showed that perceived usefulness and ease of use together had a significant positive influence on user attitudes (Attitude Toward Using), with a relationship level of 19.2%. This research provides insight into the factors that influence user attitudes towards the My APTIKOM application, which can be used as a basis for further development and improvement. In addition, this conclusion can be used by organizations, including APTIKOM, to improve IT management and ensure the applications they offer meet user needs and expectations regarding user attitudes (Attitude Toward Using), with a relationship rate of 19.2%.